Growth responses of spring barley to varying levels of drought priming - Soghadi, Zohreh Salehi; Zandi, Peiman; Wang, Yaosheng; Kaul, Hans-Peter (Frontiers in Plant Science, 2026)
IntroductionDrought-associated environmental changes pose a significant threat to global agricultural sustainability. While barley’s response to single drought events is well-documented, its adaptations to recurrent drought-rehydration cycles during the vegetative stages remain unexplored.MethodsBarely plants were subjected to five glasshouse watering regimes and harvested at six sampling times (S1-S6): full irrigation (FI, 85% soil water-holding capacity, SWHC), and four drought treatments varying in severity (mild 65% vs. severe 45% SWHC) and pattern (intermittent ID1/ID2 with rehydration vs. persistent PD1/PD2 without).ResultsPersistent drought (PD1, PD2) consistently reduced interval-specific water-use efficiency (WUEn) across all stages, while intermittent drought (ID2) enhanced WUEn during tillering. Stomatal conductance (gs) was lowest in PD treatments, with PD1 exhibiting minimum values at seedling (S1) and jointing (S5), indicating severe transpiration limitation. ID2 maintained higher gs than ID1 during seedling and tillering stages (S2, S3). However, cumulative severe stress ultimately impaired stomatal regulation in ID2, leading to ID1’s superiority by the jointing stage (S5–S6). Multivariate analysis identified stress severity as the primary initial driver of physiological disruption, revealing a fundamental shift to a biochemical stress-acclimation strategy in later stages.DiscussionThe findings delineate a dynamic recovery response under intermittent drought from a conservative, high-cost strategy under persistent drought. They suggest that applying more severe cyclic drought early (ID2, S1-S4) followed by milder cyclic stress later (ID1, S5-S6) optimizes stomatal function and productivity, enhancing resource-use efficiency under water limitation.